WTO and ‘New Issues’ - Dasgupta, Amit (NRB Economic Review, 2001)
The paper argues that WTO has not been functioning in a transparent manner and that the benefits of globalisation have not reached all countries. If Seattle is any indication, WTO is in fact 'a rich man's club'. Developed countries have been adopting the strategy of prying open the markets of developing countries while at the same time, erecting barriers that prevent access to markets in their countries to the products emanating from developing countries. In this regard, the paper looks at the 'new issues' that developed countries are keen to introduce into the WTO agenda through a new round of negotiations and argues that these would act as 'disguised protection'. By themselves, each of these issues represents an area of concern and interest for the developing countries, such as, investment, competition policy, environment, electronic commerce, etc. However, their relationship with trade is complex and this needs to be comprehensively examined in the first instance. The paper argues that it would, therefore, be both premature and inappropriate to agree to the inclusion of these so-called 'new issues' into the WTO agenda and that it is important to first implement commitments entered into in earlier rounds before taking on board fresh commitments. Much, in other words, could in fact be lost by overloading the WTO agenda. The paper also looks at the issue of labour standards, better known as 'the social clause', which some developed countries are keen to place on the WTO agenda and argues that such insistence and pressure would be counterproductive to the Multilateral Trading System as it would harm both trade and labour standards. This is not the time to bring more issues into the WTO. This is the time, on the eve of the next millennium, to reflect on our responsibilities to each other and to future generations, a time to review and repair. For too long, trade liberalization has been pursued as a goal in itself, regardless of its impact." "Millennioum Round, Game Over, No Credit Left" Friends of the Earth, 1999, The World Trade Brief, Agenda Publishers, UK.